Quantifying groundwater–surface water interactions in a proglacial valley, Cordillera Blanca, Peru. Issue 17 (21st June 2016) - Somers, Lauren D.; Gordon, Ryan P.; McKenzie, Jeffrey M.; Lautz, Laura K.; Wigmore, Oliver; Glose, AnneMarie; Glas, Robin; Aubry‐Wake, Caroline; Mark, Bryan; Baraer, Michel; Condom, Thomas
Abstract: A myriad of downstream communities and industries rely on streams fed by both groundwater discharge and glacier meltwater draining the Cordillera Blanca, Northern Peruvian Andes, which contains the highest density of glaciers in the tropics. During the dry season, approximately half the discharge in the region's proglacial streams comes from groundwater. However, because of the remote and difficult access to the region, there are few field methods that are effective at the reach scale to identify the spatial distribution of groundwater discharge. An energy balance model, Rhodamine WT dye tracing, and high‐definition kite‐borne imagery were used to determine gross and net groundwater inputs to a 4‐km reach of the Quilcay River in Huascaran National Park, Peru. The HFLUX computer programme (http://hydrology.syr.edu/hflux.html ) was used to simulate the Quilcay River's energy balance using stream temperature observations, meteorological measurements, and kite‐borne areal photography. Inference from the model indicates 29% of stream discharge at the reach outlet was contributed by groundwater discharge over the study section. Rhodamine WT dye tracing results, coupled with the energy balance, show that approximately 49% of stream water is exchanged (no net gain) with the subsurface as gross gains and losses. The results suggest that gross gains from groundwater are largest in a moraine subreach but because of large gross losses, net gains are larger in the meadow subreaches. These insights into pathways of groundwater–surface water interaction can be applied to improve hydrological modelling in proglacial catchments throughout South America. Copyright © 2016 John Wiley & Sons, Ltd.